Inovasi pembuatan Cassava Crackers berbahan Ubi Kayu pada kelompok home industri kue di desa Toaya Vunta Kecamatan Sindue - I Nengah Kundera; Amram Rede; Abd Rauf (Universitas Hamzanwadi, 2022)
Many carbohydrates are produced from the Cassava plant (Manihot esculenta Crantz) and have an essential role for humans. Cassava is used not only as a food source but also as industrial raw material, ethanol, and animal feed. To avoid the rapid deterioration of post-harvest Cassava products, Casava is very potential to be developed into various processed products and industrial raw materials. The development of the snack or snack industry has proliferated, both in type, taste, and packaging. The results of interviews conducted by a service team with the home industry Cake group in Toaya Vunta village showed that many cassava plants still have not been used optimally. This service aims to provide training and mentoring workshops on making Cassava crackers (Cassava crackers) of various flavors to mothers of the home cake industry group in Toaya Vunta village. Through the community service program, the Toaya Vunta village home industry group can be assisted in training and workshops to manufacture more modern Cassava chips with different flavors to improve their knowledge and skills. The method in this activity is to use the method of lectures, demonstrations, discussions, practices, and observations, which are the results of the activities. This activity has three stages: material presentation, direct practical assistance in making cassava chips, and the packaging process. The results of this service can improve the knowledge and skills of the home industry group of mothers in making cassava chips with various flavors. Based on these results, it is hoped that it can improve the family economy as well as support the development of creative economy businesses and community empowerment in Toaya Vunta village